Pengaruh Brand Image, Brand Love Dan E-Wom Terhadap Keputusan Pembelian Sepatu Nike Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang Angkatan 2020 - Arman, Bima Tiknanda; Rachma, N.; Athia, Ita (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the influence of Brand Image, Brand Love, and electronic word of mouth (e-WOM) on the purchasing decisions of Nike shoes among students of the Faculty of Economics and Business at the Islamic University of Malang, class of 2020. In this modern era, technological developments affect people's lifestyles, including continuously changing fashion trends. Nike, as one of the leading shoe manufacturers, has a competitive advantage with high quality and advanced technological innovation. This research uses a quantitative method with an explanatory research approach. The study population consists of students of the Faculty of Economics and Business at the Islamic University of Malang who use Nike shoes, with a sample of 110 respondents selected through snowball sampling. The results of the study indicate that simultaneously, Brand Image, Brand Love, and e-WOM significantly influence the purchasing decisions of Nike shoes. Partially, Brand Love and e-WOM have a positive and significant influence on purchasing decisions, while Brand Image does not have a significant influence. for futher researchers to expand references. Keywords: Brand Image, Brand Love, e-WOM and Purchasing Decision